Entry into grandparenthood and subjective well-being among older Europeans - Danielsbacka M.; Tanskanen A.O.; Coall D.A. (Turku Center for Welfare Research, 2022)
The birth of a grandchild is often assumed to increase subjective well-being of older adults. Previous studies, however, have been both scarce and methodologically limited. Here, associations between grandparenthood and subjective well-being (measured by self-rated life satisfaction and meaning of life scores) were investigated using data from the Survey of Health, Aging and Retirement in Europe (SHARE). SHARE is a longitudinal study of individuals aged 50 years and above from 16 countries, including five follow-up waves between 2004 and 2015 (n = 67,110 person-observations from 41,123 persons). Within-person regressions focusing on each participant’s variation in subjective well-being over time were applied to detect changes longitudinally. Becoming a grandparent was associated with increased meaning of life scores among participants. However, similar effects were not found in the case of self-rated life satisfaction. The results are discussed in relation to studies examining whether entering parenthood is associated with subjective well-being.